Mathematics as a Tool for Social Awareness and Empowerment: A Case Study from the Philippines - Miro, Eden Delight (Archīum Ateneo, 2024)
We explore mathematics as a tool for students to develop an awareness of the living conditions of communities in a rural Philippine province and to help them recognize their agency to stimulate change. Groups of college students from an urban university enrolled in a general mathematics course were given household survey data from the province. Each group built a community profile to identify their needs and vulnerabilities and crafted recommendations that may contribute to the development planning of the community.